Empowering MSME Entrepreneurship Through Digital Financial Literacy Training In Nagari Padang Lua, Agam, West Sumatera: Pemberdayaan Kewirausahaan UMKM Melalui Pelatihan Digital Financial Literacy Di Nagari Padang Lua, Kabupaten Agam, Sumatera Barat - Nurani, Khadijah; Khairi, Himmatul; Defaz, Febriyan Pratama (Institut Riset dan Publikasi Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting community economic growth; however, they still face challenges in business financial management, particularly related to digital financial literacy. This condition was also found among MSME actors in Nagari Padang Lua, Agam Regency, West Sumatra, where most business owners still used manual financial records, had not separated business and personal finances, and had not utilized digital bookkeeping applications. This community service program aimed to improve digital financial literacy and strengthen the entrepreneurial capacity of MSMEs through a Participatory Action Research (PAR)-based training approach. The implementation methods included observation, pre-test, training workshops, practical sessions on the use of digital financial applications, mentoring, and post-test evaluation. The participants consisted of 10 MSME owners from culinary, handicraft, retail, and service sectors. The results showed an improvement in participants’ digital financial literacy understanding by approximately 35–40%. Before the training, 80% of participants still used manual bookkeeping and 100% had never used digital bookkeeping applications. After the program, 70% of participants began using digital financial recording applications, 80% started separating business and personal finances, and 60% adopted QRIS and mobile banking for business transactions. The program demonstrated that digital financial literacy training could improve MSMEs’ financial management practices to become more systematic, transparent, and adaptive to digital economic transformation.